A Retrospective Study on Partial Edentulism Of Kennedy's Class Ii Classification Based on Age and Arch - MENON, GAYATHRI R; PANDURANGAN, KIRAN KUMAR (The journal of contemporary issues in business and government, 2021)
Aim: The aim of the study is to assess the analysis of partial edentulism of Kennedy's Class II among different age groups. Materials and Methods: A retrospective study was conducted among partial edentulism patients.Data collection was done by reviewing 86,000 patient’s records between june 2019 and march 2020. The parameters assessed were age, arches of Kennedy's Class II classification. The collected data were tabulated in excel sheet and imported to SPSS version 20.Descriptive statistics and Chi square test was used to determine the association between the variables. Results: In the present study, the most common age group among 60 years (34.7%). Kennedy’s Class II was more prevalent in mandibular arch (50.8%). There is no significant association between age of the patients and site with Kennedys class II (p>0.05). Conclusion: From the study we can conclude that Kennedy's class II partial edentulism was more prevalent at the age group of 60 years and above. The most affected arch was the mandibular arch. There is no significant association between age and site at which Kennedy class II was prevalent.